2015
DOI: 10.3389/fpsyg.2015.01093
|View full text |Cite
|
Sign up to set email alerts
|

How might contact with nature promote human health? Promising mechanisms and a possible central pathway

Abstract: How might contact with nature promote human health? Myriad studies have linked the two; at this time the task of identifying the mechanisms underlying this link is paramount. This article offers: (1) a compilation of plausible pathways between nature and health; (2) criteria for identifying a possible central pathway; and (3) one promising candidate for a central pathway. The 21 pathways identified here include environmental factors, physiological and psychological states, and behaviors or conditions, each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
465
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 535 publications
(490 citation statements)
references
References 77 publications
10
465
1
14
Order By: Relevance
“…Previous studies have suggested that contact with nature and natural elements improves physical health [5,55,56]. One of the underlying theories is that modern urban life causes stress [57], and chronic stress leads to physical sickness [58].…”
Section: How Does Gi Benefit Human Bodies?mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that contact with nature and natural elements improves physical health [5,55,56]. One of the underlying theories is that modern urban life causes stress [57], and chronic stress leads to physical sickness [58].…”
Section: How Does Gi Benefit Human Bodies?mentioning
confidence: 99%
“…Previous research has established that trees provide a wide variety of health benefits [55]. The presence and density of trees has been used to explore such benefits [2,3,65,72].…”
Section: Tree Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the analyses in this review examined health outcomes for which multiple other reviews find consistent ties between greenness and physical health -namely physical activity, birth and developmental outcomes, and cardiovascular outcomes [1,7,[14][15][16]. The analyses in this review represent a relatively small sample of articles using a single analytic tool to estimate residential greenness.…”
Section: Discussionmentioning
confidence: 99%
“…Physical health outcomes were divided into 18 categories. These were adapted from categories identified in previous greenness and health literature reviews [1,7,8]. The manner of data collection for physical health outcomes was grouped into three categories, based on whether data were objective (i.e., biomarkers, vital signs), expert or clinician diagnoses (i.e., electronic medical records), or subjective (i.e., self-reported health questionnaires).…”
Section: Data Extractionmentioning
confidence: 99%